2020
DOI: 10.31234/osf.io/np4t5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term memory of real-world episodes is independent of recency effects: magic tricks as ecological tasks

Abstract: How episodic memories decay is an unresolved question in cognitive neuroscience. The role of short-term mechanisms regarding the decay of episodic memories is circumscribed to set the maximum recall from which a monotonic decay occurs. However, this sequential view from the short to the long-term is not compulsory, as short-term dependent memory gains (like recency effects when memorizing a list of elements; serial-position effects) may not be translated into long-term memory differences. Moreover, producing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We have recently made a first attempt in that direction and showed that the memory of a magic trick decays over time as does that of other episodic memories. However, the serial-position differences in memorability, recency effects, that were evident after the show were no longer present later on, suggesting that short-term memory gains do not translate into the long-term ( Bestue et al, 2020 ). This preliminary work is, to our knowledge, the first scientific study of the memorability of magic tricks; and it illustrates the power that magic holds to study memory, and cognition in general, in real-world environments.…”
Section: Survey Methodologymentioning
confidence: 97%
“…We have recently made a first attempt in that direction and showed that the memory of a magic trick decays over time as does that of other episodic memories. However, the serial-position differences in memorability, recency effects, that were evident after the show were no longer present later on, suggesting that short-term memory gains do not translate into the long-term ( Bestue et al, 2020 ). This preliminary work is, to our knowledge, the first scientific study of the memorability of magic tricks; and it illustrates the power that magic holds to study memory, and cognition in general, in real-world environments.…”
Section: Survey Methodologymentioning
confidence: 97%